Teaching Reading Skills to Non-English Native Speaker Students: The Numbered Head Together (NHT) Technique and Students’ Reading Ability in Bengkulu - Yarni Valentina Gultom (International Journal of Language Teaching and Education, 2018)
The purpose of this quantitative study with a quasi-experimental approach was to examine the significant increase and difference of students’ achievement in reading after being taught through the Numbered Head Together (NHT) technique with recount texts for the second grade students at one Junior High School in Bengkulu, Indonesia. The sample of this study was 72 second- grade students divided into two classes: experimental class and control class. The experimental class was treated by being taught through the Numbered Head Together (NHT) technique while the control class was taught using conventional method. To collect the data, pre-test and post-test techniques were used. The result of paired sample t-test showed that there was a significant positive effect of Numbered Head Together (NHT) technique toward the students’ reading ability. Implications of findings and suggestions are discussed.